Depression in neurological disease – diagnostic and therapeutic problem - Koszewska, Iwona; Bzinkowska, Dorota (Przewodnik Lekarza/Guide for GPs, 2005)
Depression is one of the most frequent comorbid psychiatric disorders in patients with neurological disorders, particularly like stroke, Parkinson’s disease or Huntington’s disease. In general the pathomechanism of depression is multiple. Inspide of the range, localization and type of change, psychological and social factors are important in the development of depression in people with neurological disorders. There are some patients who fail to meet criteria for the depressive episode according to ICD-10. The most important thing is to realize the value of differential diagnostic. It helps to differ the primary depression, connecting with neurological disorders, from secondary depression which results from mental and physical disabilities or changes in life’s positions and roles. The proper diagnosis is a good reason for treating properly.